Probabilistic seismic hazard analysis Early history. - McGuire,Robin K.
Probabilistic seismic hazard analysis (PSHA) is the evaluation of annual frequencies of exceedence of ground motion levels (typically designated by peak ground acceleration or by spectral accelerations) at a site. The result of a PSHA is a seismic hazard curve (annual frequency of exceedence vs ground motion amplitude) or a uniform hazard spectrum (spectral amplitude vs structural period, for a fixed annual frequency of exceedence). Analyses of this type were first conceived in the 1960s and have become the basis for the seismic design of engineered facilities ranging from common buildings designed according to building codes to critical facilities such as nuclear power plants.
Keywords: PSHA; Seismic; Hazard; History